2005
DOI: 10.1007/s10533-005-6997-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Transport and Retention in an Arid Land Watershed: Influence of Storm Characteristics on Terrestrial–aquatic Linkages

Abstract: Arid ecosystems experience prolonged dry periods, as well as storms that vary in size, intensity and frequency. As a result, nitrogen (N) retention and export patterns may be a function of individual storm characteristics. Our objective was to determine how seasonal patterns in rainfall as well as individual storm characteristics influence N transport and retention on terrestrial hill slopes in a Sonoran Desert watershed. Regression models indicated that variation in runoff ammonium (NH 4 + ) was best explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 54 publications
5
64
0
1
Order By: Relevance
“…Research indicates that inorganic N and DOC accumulate during dry periods (Fisher et al 1987, Edmonds 2004, Welter et al 2005; we also found inorganic N, DOC, and DON to increase from June to August (active to inactive periods). In this ecosystem, July and August are hot and dry (NCDC 2005).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Research indicates that inorganic N and DOC accumulate during dry periods (Fisher et al 1987, Edmonds 2004, Welter et al 2005; we also found inorganic N, DOC, and DON to increase from June to August (active to inactive periods). In this ecosystem, July and August are hot and dry (NCDC 2005).…”
Section: Discussionsupporting
confidence: 65%
“…In this way, B. tectorum could facilitate its own spread and domination of plant communities. Alternatively, high inorganic N levels beneath stands of senesced B. tectorum, combined with B. tectorum induced increases in N cycling (e.g., Norton et al 2008), could result in increased N losses through gaseous losses (Peterjohn and Schlesinger 1990, Davidson et al 1993, Hungate et al 1997 or leaching and erosion during large, intense late season rainfall events (Loik et al 2004, Welter et al 2005. Although relatively large (>15 mm), late-season events are common in this ecosystem (1-2 mo −1 yr −1 ; NCDC 2005), climate change-predicted increases in the occurrence of large, intense precipitation events (Gordon et al 1992, Easterling et al 2000, IPCC 2001) could exacerbate losses of labile N in B. tectorum dominated communities.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the Sonoran desert is nitrogen limited (Westerman and Tucker, 1978;Whitford, 2002), we expected to observe nitrogen retention at LD and therefore low NO 3 and NO 2 runoff concentrations. However, this was not the case and the literature supports a two part explanation for the high NO 3 concentrations across sites, which can be extended to all R2 constituents: (1) solutes deposited during dry conditions accumulated within the catchment due to soil water limitations for biogeochemical activity, resulting in mobilization of accumulated solutes during rainfall and subsequent runoff (Lewis and Grimm, 2007;McCrackin et al, 2008) and (2) biogeochemical processes such as mineralization, nitrification and phosphorous retention increase in response to soil wetting, leading to accumulation of solutes in the soil between storm events and which are flushed during subsequent runoff (Austin et al, 2004;Welter et al, 2005). Both of these processes are likely to occur in the uplands and ephemeral stream channels.…”
Section: Runoff Quality Responsesmentioning
confidence: 99%
“…By making water widely available, irrigation systems increase contact between river water and sediment (and soils) and thus tend to increase nutrient processing rates. Moreover, in typical desert stream ecosystems, terrestrialaquatic interactions, while particularly important for determining stream-water chemistry, are episodic and restricted primarily to storm events , Welter et al 2005. Because processes like nitrification and denitrification frequently are stimulated when soils are wetted, the CAP ecosystem's canal system, by increasing the temporal availability of water, increases N-processing rates (e.g., Zhu et al 2004, Roach 2005.…”
Section: Urbanization's Intended and Unintended Consequencesmentioning
confidence: 99%
“…Even in mesic ecosystems where flows are more predictable and interactions between stream water and stream sediments are less temporally variable, irrigation is still likely to increase contact between stream water and upland soils, thus ensuring that hotspots are provided a steady supply of potentially rate-limiting materials. Further, because irrigation can and often does continue year-round, nutrient processing in the uplands of the IBW is not as tightly coupled to precipitation events as it is in the uplands of the surrounding desert (Welter et al 2005). The creation of the numerous artificial lakes in the IBW has also had important unintended impacts by increasing the abundance of hotspots and thus changing rates of nutrient cycling.…”
Section: Urbanization's Intended and Unintended Consequencesmentioning
confidence: 99%